A case study on limitations of commercial autosomal STR kits for determination of half-sibling by DNA analysis (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A case study was conducted to evaluate the significance of adding lineage markers for a complex kinship analysis. Additional genetic information may increase likelihood ratio values for true relationships in a pedigree, while reducing the chance of identifying false relationships. It is very difficult to establish a relationship between siblings by the statistical evaluation with autosomal STR markers. The clear discrimination of true versus false relationships is important for complex kinship cases, such as sibling testing, deficient paternity testing, missing person’s identification as well as immigration testing with the help of forensic DNA technology. This case study represents a false parent-child relation or full sibling, one individual is male and other individual is female, where matches were found at least one allele at all 23 tested autosomal STR loci with Combined Likelihood is 75,446,930.822 for Parent-Child and 284,041.488 for Half-Sibling indicates that 266 times more likely parent-child than half-sibling. In order to reach an accurate conclusion, we further included one sister of the putative brother and mother of the putative sister and these four individuals DNA samples were analyzed with X-chromosome STR kits, showing mismatches between claimed siblings in eight loci out of twelve loci and confirm that they are not parent-child. Finally we confirm that they are half-sibling and they are come from same father but different mother. This case emphasizes the necessity of lineage markers like X chromosome or Y chromosome DNA data for interpreting critical sibling cases where one of the siblings is female and their father is dead.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 148-151